Train of thought. - Williams, Fran (Architects' Journal, 2020)
The light-touch conversion was a collaboration between: Civic Architects; Braaksma & Roos,which carried out the architectural design and renovation; Inside Outside, which designed the textiles with the Textile Museum; and Mecanoo, which designed the interior, "It's considered one of the ugliest cities in The Netherlands", says Ingrid van der Heijden,partner and architect at Civic Architects.She is talking about Tilburg, the location of her Amsterdam-based practice's LocHalBibliotheek. Acting as lead architect, Civic teamed up with restoration experts Braaksma & Roos Architecten and Mecanoo for the scheme's interior design. The building's first-floor level is supported by light columns on tracks, while the second and third floors are partially carried by the new columns working together with the old structure.